Preventive Insights: The Role of Education in Enhancing Hypertension Patients' Knowledge on Heart Disease - Marwan Hatem Al-Obaidy; Zhian Abdulah; Pichayaporn Ratti (Journal of Health Innovation and Environmental Education, 2025)
Purpose of the study: The purpose of this study was to determine the effect of health education on the level of knowledge of people with hypertension about the risk factors for coronary heart disease. Methodology: The research design used is pre-experimental design with one group pre-post test design approach. The population of the study was 63 respondents. Sampling using random sampling. The sample was 39 respondents. The variables used are 2 variables, namely the independent variable with health education and the dependent variable with the level of knowledge. Data collection using a questionnaire. Statistical analysis using Wilcoxon with a significance level of 0.05. Main Findings: The results of the study showed that 22 respondents (56.41%) had insufficient knowledge before being given health education. After being given health education, 21 respondents (52.85%) had good knowledge. The p value = 0.000 ≤ α = 0.05 was obtained so that Ha was accepted. Novelty/Originality of this study: This study provides novelty by proving that structured health education interventions are able to increase the knowledge of hypertension sufferers about coronary heart disease, which has the potential to encourage earlier prevention at the community level.